The human cardiac K2P3.1 (TASK-1) potassium leak channel is a molecular target for the class III antiarrhythmic drug amiodarone - Gierten, Jakob; Ficker, Eckhard; Bloehs, Ramona; Schweizer, Patrick Alexander; Zitron, Edgar; Scholz, Eberhard P.; Karle, Christoph; Katus, Hugo; Thomas, Dierk (Naunyn-Schmiedeberg's archives of pharmacology, 2010)
Two-pore-domain (K2P) potassium channels mediate background potassium currents, stabilizing resting membrane potential and expediting action potential repolarization. In the heart, K2P3.1 (TASK-1) channels are implicated in the cardiac plateau current, IKP. Class III antiarrhythmic drugs target cardiac K+ currents, resulting in action potential prolongation and suppression of atrial and ventricular arrhythmias. The objective of this study was to investigate acute effects of the class III antiarrhythmic drug amiodarone on human K2P3.1 channels. Potassium currents were recorded from Xenopus oocytes using the two-microelectrode voltage clamp technique. Amiodarone produced concentration-dependent inhibition of hK2P3.1 currents (IC50 = 0.40 µM) with maximum current reduction of 58.1%. Open rectification properties that are characteristic to hK2P3.1 currents were not altered by amiodarone. Channels were blocked in open and closed states in reverse frequency-dependent manner. hK2P3.1 channel inhibition was voltage-independent at voltages between −40 and +60 mV. Modulation of protein kinase C activity by amiodarone does not contribute to hK2P3.1 current reduction, as pre-treatment with the protein kinase C inhibitor, staurosporine, did not affect amiodarone block. Amiodarone is an inhibitor of cardiac hK2P3.1 background channels. Amiodarone blockade of hK2P3.1 may cause prolongation of cardiac repolarization and action potential duration in patients with high individual plasma concentrations, possibly contributing to the antiarrhythmic efficacy of the class III drug.
Published online: 24 September 2009
Im Titel ist 2P tiefgestellt
Gesehen am 13.03.2023